Impact of Dairy Cooperative on Women Empowerment: A case of Nani Borvai village in Gujarat - R, Sreeni K (Journal of Agricultural Extension Management, 2020)
A case study on the role of small-scale dairy farming and the factors which help women was undertaken in Nani Borvai village, Aravalli District of Gujarat State, India. Data were collected through personal interview from 75 rural women who were involved in dairy farming. For analyzing the impact of dairy cooperatives on women’s empowerment, this study mainly focused on Decision Making, Social Index, Economic Index and Psychological Index. The intervention helped the women to earn Rs 13000 to 16000 per month as compared to Rs 5000 per month before the intervention. Better utilization of this higher earning was observed on food, clothing, health and education of children, social gathering and festivals. The women were also able to save Rs. 60,000 per year. The interventions also helped the women to improve their decision making capacity, reduce alcoholism and domestic violence, participate in group meetings and develop self-confidence. This can be further facilitated by increasing milk productivity in every household where women dominate in dairy farming management.